2005
DOI: 10.1093/pcp/pci022
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Tiller Bud Activity in Tillering Dwarf Mutants of Rice

Abstract: In this study, we analyzed five tillering dwarf mutants that exhibit reduction of plant stature and an increase in tiller numbers. We show that, in the mutants, axillary meristems are normally established but the suppression of tiller bud activity is weakened. The phenotypes of tillering dwarf mutants suggest that they play roles in the control of tiller bud dormancy to suppress bud activity. However, tillering dwarf mutants show the dependence of both node position and planting density on their growth, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
366
0
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 468 publications
(388 citation statements)
references
References 30 publications
12
366
0
10
Order By: Relevance
“…Extensive genetic studies in Arabidopsis, pea, and rice using SL-deficient and -insensitive mutants have identified components of a conserved SL signaling pathway [8][9][10][11][12][13], including rice dwarf 14 (d14) and dwarf 3 (d3). Due to the homology between D3 and the auxin and jasmonate receptors, TIR1 and COI1, and between D14 and the gibberellin receptor GID1 and the putative karrikin receptor KAI2, it had been speculated that both D3 and D14 could be candidates for the SL receptor [14].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive genetic studies in Arabidopsis, pea, and rice using SL-deficient and -insensitive mutants have identified components of a conserved SL signaling pathway [8][9][10][11][12][13], including rice dwarf 14 (d14) and dwarf 3 (d3). Due to the homology between D3 and the auxin and jasmonate receptors, TIR1 and COI1, and between D14 and the gibberellin receptor GID1 and the putative karrikin receptor KAI2, it had been speculated that both D3 and D14 could be candidates for the SL receptor [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on a series of branching mutants, such as more axillary growth (max) of Arabidopsis [37][38][39][40], ramosus (rms) mutants of pea [41][42][43], decreased apical dominance (dad) mutants of petunia [44,45] and dwarf (d) mutants of rice [46][47][48][49][50][51], have revealed strigolactone as a second messenger of auxin action on the control of AM outgrowth [52,53]. Strigolactones, a group of terpenoid lactones that have been found in root exudates of diverse plant species, are synthesized from carotenoids in roots and transported acropetally or synthesized locally to repress the outgrowth of shoot branches [38,[54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…Paradoxically, the mutants were found to have generally higher levels of auxin and lower levels of xylem cytokinin, facts difficult to reconcile with ideas about the roles of auxin and cytokinin in regulating bud outgrowth (Beveridge et al, 1997). These mutants were ramosus (rms) in pea (Pisum sativum), decreased apical dominance (dad) in petunia (Petunia hybrida), more axillary growth (max) in Arabidopsis (Arabidopsis thaliana), and particular dwarf (d) mutants in rice (Oryza sativa; Beveridge et al, 1994;Napoli, 1996;Stirnberg et al, 2002;Ishikawa et al, 2005). Grafting studies demonstrated that increased bud outgrowth in some of the mutants was caused by the loss of a long-distance mobile signal (termed SMS; Beveridge, 2006) that moved upward from lower tissues (Beveridge et al, 1994;Napoli, 1996;Foo et al, 2001;Turnbull et al, 2002).…”
mentioning
confidence: 99%
“…Likewise, RMS5, MAX3, and D17/HTD1 were found to encode CCD7 (Booker et al, 2004;Johnson et al, 2006;Zou et al, 2006). In contrast, the SMS response mutants, max2, rms4, and d3, were found to be mutated in an orthologous gene encoding an F-box protein (Stirnberg et al, 2002;Ishikawa et al, 2005;Johnson et al, 2006). Recently, the testing of putative carotenoidderived compounds led to the discovery that SMS is a strigolactone or downstream product (Gomez-Roldan et al, 2008;Umehara et al, 2008).…”
mentioning
confidence: 99%